Application of Flow‐FISH for Dynamic Measurement of Telomere Length in Cell Division. Issue 1 (1st July 2014) - Borisov, Vyacheslav I.; Korolkova, Olga Y.; Kozhevnikov, Vladimir S.
Abstract: This method makes it possible to measure the fluorescence of a DNA probe in cells with known division number and targeted surface antigen. In fact, this method is a combination or consistent application of three other methods: cell tracking by vital dye, surface immunophenotyping, and flow‐FISH. The idea in developing this method was to study telomere length changes in cells with known surface antigen after every new cell division. First, the in vitro cell culturing and staining with CFSE vital dye are performed. Then, cells are stained with surface MAbs labeled with biotin, followed by incubation with streptavidin‐labeled fluorochrome. After that, cells are fixed with BS 3 reagent followed by the flow‐FISH procedure with PNA‐probe complementary to telomere DNA repeats. Finally, in one tube, it is possible to determine telomere length in surface antigen–labeled cells that have made the exact same number of divisions after incubation. Curr. Protoc. Cytom . 69:8.14.1‐8.14.10. © 2014 by John Wiley & Sons, Inc.